Islamic Exceptionalism : How the Struggle Over Islam is Reshaping the World - Shadi Hamid (New York St. Martin's Press, 2016)
From the founding of Islam in the seventh century, there had always been a dominant Muslim empire, or "caliphate." But in 1924, the Ottoman Caliphate was formally abolished. Since then, there has been an ongoing struggle to establish a legitimate political order in the Middle East. At the center of that struggle is the vexing problem of religion and its role in political life. In Islamic Exceptionalism, Brookings Institution scholar and acclaimed author Shadi Hamid offers a novel and provocative argument on how Islam is, in fact, "exceptional" in how it relates to politics, with profound implications for how we understand the future of the Middle East. With unprecedented access to Islamist activists and leaders across the region, Hamid argues for a new understanding of how Islam and Islamism shape politics - and how the practice of politics shapes Islam. Despite the hopes of the Arab Spring, ideological and religious polarization has actually worsened. Divides among citizens aren't just about power but are products of fundamental disagreements over the very nature and purpose of the modern nation state. Drawing on hundreds of hours of interviews across the region, Hamid examines different models of reckoning with the problem of religion and state, including the terrifying - and alarmingly successful - example of ISIS. Offering a panoramic and ambitious interpretation of the region's descent into violence, Islamic Exceptionalism is a vital contribution to our understanding of Islam's past and present, and its outsized, exceptional role in modern politics. We don't have to like it; but we have to understand it, because it will continue to be a force that shapes not just the region, but the West as well, in the coming decades.
Include Notes and Index.
How the Struggle Over Islam is Reshaping the World.
Keywords: Arab countries -- Middle East -- Politics and government -- Islam and politics